THEORETICAL AND METHODOLOGICAL REASONING OF THE SET OF COMPONENTS OF FINANCIAL AND ECONOMIC SECURITY OF SOCIO-ECONOMIC SYSTEMS - NYZHNYK, OLEH; NYZHNYK, IRYNA; LYSAK, VIKTOR (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Based on the scientific views of scientists and practitioners identified the main purpose of the concept of financial and economic security of socio-economic systems, including higher education institutions. The urgency of ensuring the financial and economic security of domestic higher education institutions is primarily due to the following factors: maintaining financially effective resilience to external and internal stimuli and threats; improving the efficiency of management; ensuring the optimal number of of teaching staff; minimizing the impact of the COVID-19 pandemic and military aggression by the Russian Federation; the need to protect the information space of participants in the educational process; ensuring a high level of qualification of scientific, pedagogical and support staff; increasing the competition of graduates of higher education institutions. The authors present their own views on the separation of components of financial and economic security of higher education institutions that are responsible for various areas of operation and their constituent objects, such as: intellectual and personnel, technical and technological, financial and investment, material and technical, information and communication, regulatory, educational and methodical, socio-cultural, security, energy, economic areas. In the article the authors formed tasks, criteria and indicators, objects and subjects, measures and principles of provision, components of evaluation and built an algorithm to increase the level of financial and economic security of socio-economic systems, on the example of higher education institutions. The algorithm presented by the authors contains 5 adjustment tools (feedbacks): adjusting the structure of negative factors in determining their structure and their distribution according to subjective and objective criteria; adjustment of the developed preventive measures during their development and implementation; adjustment after analysis of the functional results of the implemented measures; adjustments in assessing the economic efficiency of the implemented measures; maintaining a sufficient level of financial and economic security to adapt to changes in the internal and external environment of higher education institution.